Precautionary measure of Lis Pendens and a recent decision of the Constitutional Court - Hurtado Reyes, Martín Alejandro (2019)
This article analyzes the judgment of the Constitutional Court in the matter of Docket No. 06920-2013-PA/TC Lima, in which, by a majority decision, the Court dismissed the appeal for amparo filed against the judgment that discussed the possibility of lifting the preventive measure of lis pendens dictated in a labor proceeding, on a property that was subsequently granted in ownership to a third person. In this regard, the article examines the unsuitable nature of the precautionary measure of lis pendens to guarantee decisions related to labor debts, as well as their lack of utility to prioritize the payment of credits. Furthermore, it questions the fact that the adjustment of the referred measure with respect to the protected interest was not respected; and that the precautionary measure of lis pendens was not lifted thereby seriously affecting the property rights of the party who obtained the property in an auction.